Analysis of the roof of an autonomous house for efficient use of wind energy - Bekbaev, A. B.; Shakenov, K. B.; Titkov, V. V. (EAI Endorsed Transactions on Energy Web, 2018)
In this paper considered the form of an autonomous house roof for effective use of the wind kinetic energy in the application of closed wind power plant. The elements of the wind power plant and the roof of the autonomous house are transformed into a finite element model for aerodynamic calculation. In the calculations used various versions of the autonomous house roof to find the optimal conditions for increasing the energy efficiency factor of the energy carrier. The results of this work can be used in the design of autonomous houses.
Keywords: wind energy; closed wind power plants; increase in wind energy conversion factor; efficient converters